2006
DOI: 10.1007/s10643-005-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Family-Centered Intervention for Young Children at-risk for Language and Behavior Problems

Abstract: This study investigated the effects of a family-centered intervention that involved parents in weekly assessments and daily routine activities for promoting young children's language and behavior. Forty-one 3-5-year-old children at-risk for language and behavior problems, recruited from three developmental pre-schools, were randomly assigned to a control and an intervention group that received parent-professional support. Analyses of covariance (ANCOVAs) were used to examine whether groups differed on post-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 16 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Planning home visits together with parents also promotes adult learning by offering opportunities to increase parents' self-efficacy about supporting their children's development (ZTT, 2012). Home visitors need to know how to collaborate with families in ways that are respectful of a variety of cultural practices (Barrera & Corso, 2003) while guiding parents in choosing home visit topics and planning activities to do with their children (Chao, Bryan, Burstein, & Ergul, 2006;Dunst & Dempsey, 2007). This will keep home visits focused on the child outcomes and parenting interactions that parents value most.…”
Section: Teaching Adultsmentioning
confidence: 99%
“…Planning home visits together with parents also promotes adult learning by offering opportunities to increase parents' self-efficacy about supporting their children's development (ZTT, 2012). Home visitors need to know how to collaborate with families in ways that are respectful of a variety of cultural practices (Barrera & Corso, 2003) while guiding parents in choosing home visit topics and planning activities to do with their children (Chao, Bryan, Burstein, & Ergul, 2006;Dunst & Dempsey, 2007). This will keep home visits focused on the child outcomes and parenting interactions that parents value most.…”
Section: Teaching Adultsmentioning
confidence: 99%
“…). Research among the families of children with some conditions indicates that parents' increased empowerment is associated with improved resources (Øien et al ., ), family cohesion, relations and functioning (Scheel and Rieckmann, ) and reduced parenting stress (Øien et al ., ) as well as with children's improved psychosocial, physical and social development (Chao et al ., ). Positive associations have been found between parental empowerment and parents' experiences of the accessibility of basic services and sufficiency of support (Halme et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated parental empowerment in ambulatory care (Tourigny et al 2008) or in paediatric rehabilitation (Øien et al, 2009) or in families with children with conditions such as cerebral palsy (Rentinck et al, 2009) or diabetes (Robinson et al 2011). Research among the families of children with some conditions indicates that parents' increased empowerment is associated with improved resources (Øien et al, 2009), family cohesion, relations and functioning (Scheel and Rieckmann, 1998) and reduced parenting stress (Øien et al, 2009) as well as with children's improved psychosocial, physical and social development (Chao et al, 2006). Positive associations have been found between parental empowerment and parents' experiences of the accessibility of basic services and sufficiency of support .…”
Section: Introductionmentioning
confidence: 99%
“…Bakermans- Kranenburg, Van Ijzendoorn, & Juffer, 2003), on-going monitoring of growth and challenges (e.g. Chao, Bryan, Burstein, & Ergul, 2006), as well as emphasis on decreasing stress and anxiety (e.g. Meyer et al, 1994) have all been found to be effective components of early intervention programmes.…”
Section: Discussionmentioning
confidence: 99%